2020
DOI: 10.1159/000507400
|View full text |Cite
|
Sign up to set email alerts
|

Prior Therapeutic Experiences, Not Expectation Ratings, Predict Placebo Effects: An Experimental Study in Chronic Pain and Healthy Participants

Abstract: Introduction: Many clinical trials fail because of placebo responses. Prior therapeutic experiences and patients' expectations may affect the capacity to respond to placebos in chronic disorders. Objective: The scope of this study in 763 chronic orofacial pain and healthy study participants was to compare the magnitude and prevalence of placebo effects and determine the putative role of prior therapeutic experiences vs. expectations. Methods: We tested placebo propensity in a laboratory setting by using 2 dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 51 publications
8
55
0
Order By: Relevance
“…Nevertheless, the methodology employed here has repeatedly proven successful in inducing placebo effects in the past 9,34,44 . Moreover, other studies of comparable sample size have reported larger placebo effects 27,28 . It is therefore possible www.nature.com/scientificreports/ that the scarcity of measures associated with placebo responses was due to their small effect size, and the regression analysis for nocebo responses was more successful because of the higher effect sizes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, the methodology employed here has repeatedly proven successful in inducing placebo effects in the past 9,34,44 . Moreover, other studies of comparable sample size have reported larger placebo effects 27,28 . It is therefore possible www.nature.com/scientificreports/ that the scarcity of measures associated with placebo responses was due to their small effect size, and the regression analysis for nocebo responses was more successful because of the higher effect sizes.…”
Section: Discussionmentioning
confidence: 78%
“…Fourth, the assumptions regarding the association of trait variables and outcomes are comparatively basic, and we did not consider more complex psychological process models recently applied to expectation effect research, such as the Elaboration Likelihood Model of persuasion 45 . Relatedly, expectations themselves were not assessed despite conceptual merit 6 , while empirical merit is more ambiguous 27,46 . Here, we opted against querying expectation ratings due to the risk of amplifying demand characteristics and carry-over effects inherent in a cross-over design 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding predictors for nocebo responses, a relationship with dispositional pessimism 14 , and neuroticism 18 has been reported. In general, placebo effects have received far more attention than nocebo effects 7 , including recent studies involving large cohorts 19,20 . However, the importance of nocebo effects for quality of life, medication adherence and ultimately treatment success are being increasingly acknowledged 21 .…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference in placebo analgesic responses in FM patients and HCs which is consistent with the few studies comparing placebo effects to experimental stimuli in pain patients and healthy participants. The most recent and largest behavioral study of this kind reported no differences in placebo effects between 363 chronic pain patients with temporomandibular disorder and 400 healthy controls [12]. Comparable placebo effects have also been reported between healthy participants and patients with episodic migraine [30], irritable bowel syndrome (IBS) [28], and atopic dermatitis [24].…”
Section: Placebo Effects On Experimental Pain In Healthy and Chronic mentioning
confidence: 99%